1995
DOI: 10.1007/bf00195707
|View full text |Cite
|
Sign up to set email alerts
|

Responses to iron deficiency in Arabidopsis thaliana: The Turbo iron reductase does not depend on the formation of root hairs and transfer cells

Abstract: Arabidopsis thaliana (L.) Heynh. Columbia wild type and a root hair-less mutant RM57 were grown on iron-containing and iron-deficient nutrient solutions. In both genotypes, ferric chelate reductase (FCR) of intact roots was induced upon iron deficiency and followed a Michaelis-Menten kinetic with a Km of 45 and 54 microM FeIII-EDTA and a Vmax of 42 and 33 nmol Fe2+.(g FW)-1.min-1 for the wild type and the mutant, respectively. The pH optimum for the reaction was around pH 5.5. The approximately four fold stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…Decreases in the activity of the FC-R in Fe-deficient plants at high pH have been reported before for intact plants of peanut (Romheld and Marschner, 1983), apple (Ao et al, 1985), Ficus benjamina (Rosenfield et al, 1991), G. urbanum (Schmidt and Janiesch, 1991a), and A. thaliana (Moog et al, 1995). However, in most of these cases the pH www.plantphysiol.org on March 24, 2019 -Published by Downloaded from Copyright © 1996 American Society of Plant Biologists.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Decreases in the activity of the FC-R in Fe-deficient plants at high pH have been reported before for intact plants of peanut (Romheld and Marschner, 1983), apple (Ao et al, 1985), Ficus benjamina (Rosenfield et al, 1991), G. urbanum (Schmidt and Janiesch, 1991a), and A. thaliana (Moog et al, 1995). However, in most of these cases the pH www.plantphysiol.org on March 24, 2019 -Published by Downloaded from Copyright © 1996 American Society of Plant Biologists.…”
Section: Discussionmentioning
confidence: 81%
“…Vol. 11 O, 1996 Briiggemann andMoog, 1989) and subsequently in strategy I plants such as tomato (Buckhout et al, 1989;Briiggemann et al, 1990;Holden et al, 1991Holden et al, , 1992Valenti et al, 1991), bean (Schmidt and Janiesch, 1991b), Plantago (Schmidt et al, 1990), Geum urbanum (Schmidt and Janiesch, 1991a), Vigna unguiculata (Briiggemann et al, 1993), and Arabidopsis tkaliana (Moog et al, 1995). However, the PM from Fe-deficient plants usually exhibits FC-R activities biochemically similar to those of PM from control plants.…”
mentioning
confidence: 99%
“…1) and not dueto the mutation per se. Moog et al (1995) suggested that, since the elongation and maturation zones of roots are the major sites of Fe reduction, large root systems consisting of a greater proportion of older root than small root systems may effectively reduce the activity of ferric-chelate reductase when expressed on a fresh weight basis. Despite this possible confounding factor, we found that manl seedlings do not increase their ferric-chelate reductase activity when Fe deficient, suggesting that the enzyme is either constitutively expressed or unable to be induced by Fe deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Roots of the Poaceae (grasses) use a different strategy involving the secretion of phytosiderophores and subsequent uptake of the Fe(III)-phytosiderophore complex (strategy II) (Schmidt, 1999). Fe deficiency substantially increased both the length and number of root hairs in Arabidopsis, the response being seen within 24 h of transferring the seedlings to -Fe medium (Moog et al, 1995).…”
Section: Root Hair Length and Densitymentioning
confidence: 99%